Angiotensin-(1-7)-Mediated Signaling in Cardiomyocytes - Enéas R. M. Gomes; Robson A. S. Santos; Silvia Guatimosim (International Journal of Hypertension)
The Renin-Angiotensin System (RAS) acts at multiple targets and has its synthesis machinery present in different tissues, including the heart. Actually, it is well known that besides Ang II, the RAS has other active peptides. Of particular interest is the heptapeptide Ang-(1-7) that has been shown to exert cardioprotective effects. In this way, great compilations about Ang-(1-7) actions in the heart have been presented in the literature. However, much less information is available concerning the Ang-(1-7) actions directly in cardiomyocytes. In this paper, we show the actual knowledge about Ang-(1-7)-mediated signaling in cardiac cells more specifically we provide a brief overview of ACE2/Ang-(1-7)/Mas axis; and highlight the discoveries made in cardiomyocyte physiology through the use of genetic approaches. Finally, we discuss the protective signaling induced by Ang-(1-7) in cardiomyocytes and point molecular determinants of these effects.